Enhancement of sensitivity in surface plasmon resonance - David Levy; Robert E. Camley (AIP Advances)
We aim to find the ideal parameters that will yield the best sensitivity for surface plasmon resonance measurements using attenuated total reflection. Several geometries and parameters are explored. Prism and metal choices are explored over a range of relative permittivities. In addition, the effect of frequency on sensitivity and, finally, the addition of layers of nanomaterials are explored as an aid to sensitivity. The results presented are appropriate for a sensing medium (water) with a refractive index of 1.33 and small changes due to an added analyte. The maximum sensitivity of the proposed structure is found to be 580 (degree/refractive index unit) for a wavelength of 633 nm. This is substantially larger than the typical value found in current applications.